INVESTIGATION OF FACTORS INFLUENCING TUBERCULOSIS DEVELOPMENT IN CHILDREN ACCORDING TO TUBERCULOSIS CONTACT HISTORY - Khakimov Abdulatif Abduvali o‘g‘li; Djurabaeva Mukhabbat Khusanovna (TADQIQOTLAR, 2026)
Background: Tuberculosis (TB) remains a significant global health concern, especially among children. Understanding the risk factors associated with TB development in pediatric populations is crucial for effective prevention and management. Objective: This study aims to compare risk factors between children who have direct contact with TB patients and those who do not, with the goal of identifying key determinants of TB susceptibility. Methods: We conducted a analysis of pediatric TB cases from medical records. Participants were divided into two groups: Group A (children with direct TB exposure) and Group B (children without direct TB exposure). Demographic, clinical, and environmental variables were assessed. Results: Preliminary findings indicate that children with direct contact with TB patients are at higher risk of developing TB. Key risk factors include: Household Exposure - Children living in close proximity to active TB cases face increased transmission risk; Malnutrition - Poor nutritional status weakens the immune system, making children more susceptible to TB infection; Crowded Living Conditions - Overcrowded households facilitate TB transmission. Conclusion: Our study underscores the importance of targeted interventions for high-risk pediatric populations. Early case detection, nutritional support, and infection control measures are essential in reducing TB incidence among children.